AQUEOUS PHASE REFORMING OF SORBITOL OVER Ni/Al2O3DOPED WITH Ca AND Mg FOR VALUE-ADDEDCHEMICALS PRODUCTION - MD RADZI, MOHAMAD RAZLAN (2019)
Production of C2-C6value-added chemicalsderived from sorbitol via aqueous phase reforming (APR) wasconsidered as promising green technologydue to positive benefits of aqueous phase reforming, notably low temperature requirement and high yield of products. 18 samples of 10% Ni/Al2O3were synthesized, and 0.5 to 5% of dopantofCa and Mgwereutilized to help stabilize Ni/Al2O3in aqueous condition, where sonochemical method was selected and used to further improve the physiochemical properties of the catalyst, while comparing with wet impregnation method. Characterization techniques such as TGA, FESEM, BET, XRD and H2-TPR were implemented, where increased addition of Ca and Mg showedsome increase in particle agglomeration and crystal size, reduce surface area, reduces reduction temperature